Current status and future directions of U.S. genomic nursing health care policy - Kurnat-Thoma, Emma (Nurs Outlook, 2021)
BACKGROUND: As genomic science moves beyond government-academic collaborations into routine healthcare operations, nursing’s holistic philosophy and evidence-based practice approach positions nurses as leaders to advance genomics and precision health care in routine patient care. PURPOSE: To examine the status of and identify gaps for U.S. genomic nursing health care policy and precision health clinical practice implementation. METHODS: We conducted a scoping review and policy priorities analysis to clarify key genomic policy concepts and definitions, and to examine trends and utilization of health care quality benchmarking used in precision health. FINDINGS: Genomic nursing health care policy is an emerging area. Educating and training the nursing workforce to achieve full dissemination and integration of precision health into clinical practice remains an ongoing challenge. Use of health care quality measurement principles and federal benchmarking performance evaluation criteria for precision health implementation are not developed. DISCUSSION: Nine recommendations were formed with calls to action across nursing practice workforce and education, nursing research, and health care policy arenas. CONCLUSIONS: To advance genomic nursing health care policy, it is imperative to develop genomic performance measurement tools for clinicians, purchasers, regulators and policymakers and to adequately prepare the nursing workforce.